1999
DOI: 10.1002/(sici)1097-0134(19991115)37:3<388::aid-prot7>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional solution structure ofAesculus hippocastanum antimicrobial protein 1 determined by1H nuclear magnetic resonance

Abstract: Aesculus hippocastanum antimicrobial protein 1 (Ah-AMP1) is a plant defensin isolated from horse chestnuts. The plant defensins have been divided in several subfamilies according to their amino acid sequence homology. Ah-AMP1, belonging to subfamily A2, inhibits growth of a broad range of fungi. So far, a three-dimensional structure has been determined only for members of subfamilies A3 and B2. In order to understand activity and specificity of these plant defensins, the structure of a protein belonging to sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…Closer examination of this sequence and the corresponding sequence of MtDef4 revealed the presence of a highly conserved γ-core motif, the hallmark feature of the three-dimensional structure of disulfide-containing antimicrobial peptides from evolutionarily diverse organisms [22]. The γ-core motif of both defensins satisfied the consensus sequence GXC(X 3–9 )C and were part of the predicted three-dimensional solvent-exposed β2–β3 loop region of each protein [20], [28], [29], [30], [31], [32]. Plant defensins also contain the α-core motif with a consensus sequence GXC(X 3–5 )C (Figure 1).…”
Section: Discussionmentioning
confidence: 89%
“…Closer examination of this sequence and the corresponding sequence of MtDef4 revealed the presence of a highly conserved γ-core motif, the hallmark feature of the three-dimensional structure of disulfide-containing antimicrobial peptides from evolutionarily diverse organisms [22]. The γ-core motif of both defensins satisfied the consensus sequence GXC(X 3–9 )C and were part of the predicted three-dimensional solvent-exposed β2–β3 loop region of each protein [20], [28], [29], [30], [31], [32]. Plant defensins also contain the α-core motif with a consensus sequence GXC(X 3–5 )C (Figure 1).…”
Section: Discussionmentioning
confidence: 89%
“…Among characterized defensins, DgDEF1 shows the highest homology with representatives of class A3, an aluminum-induced tobacco protein [52], a defensin of Dahlia merckii [53], [54] and the Antifungal Protein 1 from radish seeds (RsAFP1) [55], [56]. It shows lower homology with the A2 defensin from Aesculus hippocastanum [57] and even lower homology with the B2 thionins from wheat and barley [58]. Detailed analysis revealed that DgDEF1 is a member of a small nodule-specific defensin subfamily including DgDEF2 ( Dgc845 ; Table S1A and Table 1; GenBank accession no.…”
Section: Resultsmentioning
confidence: 99%
“…There are two Gly residues at positions 13 and 34, in addition to the conserved Cys residues, a Glu residue at position 29 and a conserved aromatic residue at position 11 (Broekaert et al, 1995; Meyer et al, 1996; Artlip and Wisniewski, 2001). Studies of their three-dimensional structure have shown that it comprises a triple-stranded β-sheet with an α-helix in parallel (Bruix et al, 1993, 1995; Bloch et al, 1998; Fant et al, 1998, 1999; Almeida et al, 2000). They can be expressed during storage and reproduction, being related to antibacterial and antifungal activities (Broekaert et al, 1997; Wijaya et al, 2000; Stotz et al, 2009), environmental stress response (Maitra and Cushman, 1998), as well as signaling molecules, including methyl jasmonate, ethylene, and salicylic acid (Hanks et al, 2005), and regulating the innate immune system (de Beer and Vivier, 2011).…”
Section: Fruit Antimicrobial Peptidesmentioning
confidence: 99%